Leaf area to fruit mass ratio determines the time of veraison in Sauvignon Blanc and Pinot Noir grapevines. (22nd September 2014) - Parker, A.K.; Hofmann, R.W.; van Leeuwen, C.; McLachlan, A.R.G.; Trought, M.C.T.
Abstract Background and Aims The extent to which the carbohydrate source–sink ratio influences the time of veraison of different Vitis vinifera L. cultivars was studied for Sauvignon Blanc and Pinot Noir. The aims were to: (i) determine how changing the leaf area: fruit mass (LA : FM) ratio shortly after fruitset alters the timing of veraison; (ii) establish the relative importance of adjusting the vine yield or the leaf area on the timing of veraison; and (iii) evaluate the relative effect on the timing of veraison, leaf area and yield parameters of the two cultivars at similar LA : FM ratios. Methods and Results Four cane, vertical shoot positioned trained vines were trimmed shortly after fruitset to retain six or 12 leaves per shoot and thinned by removing 0, 50 or 75% of the bunches. The timing of veraison was assessed by colour change for Pinot Noir, berry softness for Sauvignon Blanc and the day at which a mean of 8°Brix was reached for both cultivars. Manipulating leaf area had a greater effect on the date of veraison than crop removal, which had no effect, except when vines were trimmed to six leaves. Sauvignon Blanc was always later than Pinot Noir for the time to reach 8°Brix at all LA : FM ratio manipulations. Conclusions Restricting potential carbohydrate sources post‐flowering delayed veraison, while removing crop had less influence. Significance of the Study Reduced leaf area can delay the time of veraison, which could counter the earlier timing that could occur from climate change or warmer than average seasons. Conversely, increased leaf area could enable target soluble solids to be achieved in cooler seasons.